The correlation between weight divisions and methods used by winning mixed martial arts athletes - Ma, C. (The Sport Journal, 2025)
This study analyzes the correlation between weight divisions and the methods used by 174 top-ranking Ultimate Fighting Championship (UFC) elite athletes to victory, thus providing valuable information to help coaches and athletes formulate their training plans and competition strategies. It uses descriptive statistical analysis to present essential data in answer to a number of research questions. A Mann-Whitney U test was conducted to test the difference between male and female athletes within the same weight divisions, with a Kruskal-Wallis test revealing differences among weight divisions for each sex. Spearman`s correlation and Linear Regression tests were then used to analyze the relationship between these weight divisions and the methods used by winning athletes. The results indicated the following ratios for success: Knockout (KO)/Technical Knockout (TKO) (40.21%±22.27), Decision (36.78%±20.88), and Submission (23.01%±18.36). Spearman`s rho bivariate correlation test showed that the weight divisions for male athletes had a positive correlation with KO/TKO and a negative correlation with Decision and Submission regarding the methods leading to their success. However, there was no correlation between weight divisions for female athletes and their winning methods. Linear regression test results indicated linear correlations between the independent and dependent variables and created regression models for the correlation between the weight divisions of male athletes and their methods. The present study aims to provide coaches and athletes with valuable reference points concerning weight divisions and victory, thus enabling them to optimize training plans and competition strategies and change weight divisions to secure competitive advantages. Sports fans would also be able to make more logical predictions concerning the possible victory methods of their favorite athletes.